Experimental evidence of Phase Control method in chaotic Semiconductor Laser - Ibrahim, Raghad I.; Al Naimee, Kais A. M.; Yaseen, Sameer Kh. (Iraqi Journal of Science, 2019)
we study how to control the dynamics of excitable systems by using the phase control technique.We study how to control nonlinear semiconductor laser dynamics with optoelectronic feedback using the phase control method. The phase control method uses the phase difference between a small.added frequenc y and the main driving frequency to suppress chaos, which leads to various periodic orbits. The experimental studying for the evaluation of chaos modulation behavior are considered in two conditions, the first condition, when one frequency of the external perturbation is varied, secondly, when two of these perturbations are changed. The chaotic system becomes regular under one frequency or two frequencies, But in two frequencies, phase control showed an excellent ability to maintain regular behavior in chaotic window and reexcite chaotic behavior when destroyed. This dynamics of the laser output are analyzed by time series and bifurcation diagram.